REVITALISASI TEMPAT WISATA WATOE DELEAN PRIGEN SEBAGAI PARIWISATA UNGGULAN DESA SUKORENO - Yurilla Endah Muliatie; Sri Suprapti; Gita Fitri Sakinah Putri; Putri Nurlaili Susanti; Linda Asih Pratiwi; Gani Sutrisno (Universitas Islam Malang, 2023)
The purpose of this service activity is to revive and tidy up this tourist spot so that it can be enjoyed by the general public, both local and outside the region. This is because this tourist spot has changed its function to become a resting place since the Covid-19 pandemic. Now the tourist spot wants to be reused as a tourist spot according to the wishes of the Kebon Alas hamlet community. The method of implementing this activity was carried out through socialization, education, training, and evaluation for residents of Kebonalas, Sukoreno, and Prigen hamlets. The results of this activity include an increase in community understanding of the importance of tourism awareness, which is evident through the community's enthusiasm to be more active in promoting this tourist spot by holding activities such as competitions and gymnastics at this place. In addition, the management of the management is improved properly, such as the expansion of the parking area, the addition of trash bins, and the addition of writings that can attract visitors, as well as promotion on social media, this tourist spot is increasingly widely known, as evidenced by the number of visitors who come to this place, both individually and in groups.